Impact of subducting slabs on the mantle transition zone - Zhang, Xiaoqing; Thybo, Hans; Artemieva, Irina M.; Xu, Tao (Copernicus GmbH, 2024)
The mantle transition zone (MTZ) bounded by the 410-km discontinuity (d410) and 660-km discontinuity (d660), controls material and heat exchange between the upper and lower mantle. The phase transformations in MTZ are affected by subducting slabs that reach the transition zone by the exothermic phase transitions from olivine to wadsleyite around d410 and from wadsleyite to ringwoodite around 520 km depth (d520), as well as the endothermic phase transition from ringwoodite to post-spinel phases around 660 km depth which has long been considered as a likely cause of a viscosity increase below d660. However, how subducting slabs impact the mantle transition zone (MTZ) is debated. The Pacific-Asia subduction system is ideal for studying slab impact on the MTZ. It includes multi-stage subduction of the modern Pacific plate and the earlier Izanagi plate, and seismic tomographic models image flattening of the Izu-Bonin and Japan-southern Kurile slabs at the base of the MTZ. We calculate receiver function images of the MTZ based on data recorded by 322 broadband seismic stations in Northeastern China. We image the area of the flattened slab inside the MTZ but not the effects where the slab interacts with d410. Our results show that the d410 is flat and 5-10 km deeper than the global average within the area covered by our data and the average depth of d660 is about 670 km, which is consistent with previous results and may be explained by temperature-chemical effects. A complex d520 is clearly observed which we interpret as the top boundary of the flattened slab although it may also be caused by unstable temperature conditions.